Exploring the transition: a case study of RPL students in a postgraduate programme - Brenner, Aimee (Organisational Psychology, 2021)
There has been a movement across South Africa's education sector to widen access and participation in higher education (HE). Recognition of Prior Learning (RPL) programmes offer an opportunity to do so by providing access to HE to those who do not necessarily have the prerequisite requirements. There is still much to learn regarding RPL programmes and the unique needs and challenges of RPL students, as most of these programmes are still in the pilot stage. This study is specifically concerned with the transition of RPL students into postgraduate HE, as little research has been conducted on this topic. To gain a deeper understanding of RPL student transition, the researcher followed a case-study approach in which the experiences of RPL students enrolled in an online postgraduate diploma programme in management in marketing (PgDipMM) at a South African university were investigated. The programme piloted a novel RPL assessment and selection process which aimed to address criticisms of previous models. Qualitative data was obtained through eight open-ended, in-depth interviews with RPL students enrolled in the programme. Using a thematic analysis approach, nine key themes were identified as possible mechanism that facilitated RPL students' successful transition into the postgraduate diploma and six themes that did not. Findings indicated that, to a large extent, the novel RPL assessment and selection process appeared to have facilitated RPL students' successful transition into a postgraduate diploma through technical preparation and building students' confidence in their abilities. Possible enablers and barriers to RPL students' successful transition were also identified and discussed. In short, the enablers included learner maturity, transference of prior knowledge and skills, social support, sense of belonging, access to effective resources and financial security. Conversely, the barriers included academic difficulties, under preparedness for the intensity of HE and time restrictions. The study had theoretical and practical implications in that it contributed to our understanding of RPL student transition to HE and provided suggestions for ways in which their successful transition can be facilitated